TREATMENT OF PERIPARTUM CARDIOMYOPATHY (REVIEW) - N. T. Vatutin; G. G. Taradin; L. G. Popelnukhina; Y. P. Gritzenko; I. A. Sidorenko (SINAPS LLC, 2017)
The presented review concerns discussion about current insights into treatment of peripartum cardiomyopathy. The definition of peripartum cardiomyopathy and general issues about diagnosis and pathogenesis of the disorder are provided at the head of the review. Particularly, the role of the system «prolactin - cathepsin D - prolactin 16 kDa» in cardiomyopathy development is disclosed. The general approaches to management of the patients are highlighted. The review provides detailed data about indications, adverse effects and derived clinical experience concerning the main pharmacological drugs which had been used in peripartum cardiomyopathy treatment given their possible unfavorable influence on fetus maturation and maternal lactation. The detailed description is provided on diuretics including loop, thiazide and potassium-sparing drugs. It was noted relative safety and efficiency of nitrates and hydralazine in conditions of limited choice from vasodilator group and, particularly, angiotensinconverting-enzyme inhibitors and angiotensin-II receptor blockers which are contraindicated in pregnancy. A special attention is paid to the group of inotropic drugs: levosimendan, milrinone, and cardiac glycosides. The role of β-blockers and ivabradine is disclosed in heart failure treatment of peripartum cardiomyopathy. Anticoagulants were presented in details given that these drugs are justified in severe cardiac chambers dilation, decrease in ejection fraction, and in presence of intracardiac thrombosis. The place of antiarrhythmic drugs administrating in various cardiac rhythm disorders is discussed in the review. The data is given with account of potential influence on fetus in antenatal peripartum cardiomyopathy in which lidocaine and sotalol are the most preferable drugs; adenosine, quinidine, and flecainide are useful with caution, but amiodarone and dronedarone are absolutely contraindicated. Taking into account proposed pathogenic mechanisms of this cardiomyopathy, the information about pharmacological drugs directed to correction of possible links of development mechanism of this pathology is introduced. On the basis of analyzed data authors discuss relevance, indications and side effects of immunosuppressive therapy, immunoglobulin, pentoxifylline, and prolactin secretion inhibitors - bromocriptine and cabergoline. The experience of cardiac transplantation is specified in patients with refractory peripartum cardiomyopathy, and issues of delivery are highlighted in women suffering from this disease.